1999
DOI: 10.1046/j.1439-0442.1999.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

No Expression of Angiotensin II Receptors and Angiotensin‐Converting Enzyme in Myxomatous Canine Mitral Valve Leaflets. An Autoradiographic Study

Abstract: The renin-angiotensin system, including angiotensin (Ang) II and angiotensin-converting enzyme (ACE), plays an important role in cardiac fibrous tissue formation. Since changes in valvular collagen are a central part of myxomatous mitral valve disease in the dog, we speculated that Ang II and ACE might play a role in the pathogenesis of this disease.In 10 mitral valves, five with and five without clear myxomatous changes, the presence and distribution of Ang II receptors and ACE was examined autoradiographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recent autoradiographic studies indicate that in canine atrioventricular valves as opposed to rat valves, angiotensin II receptors and ACE are scant. 25 This finding is at odds with the theory that local RAASs in the valves contribute to progressive valvular degeneration. In contrast, the canine myocardium has a comparably high concentration of angiotensin II receptors and ACE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent autoradiographic studies indicate that in canine atrioventricular valves as opposed to rat valves, angiotensin II receptors and ACE are scant. 25 This finding is at odds with the theory that local RAASs in the valves contribute to progressive valvular degeneration. In contrast, the canine myocardium has a comparably high concentration of angiotensin II receptors and ACE.…”
Section: Discussionmentioning
confidence: 99%
“…85 The same group reported no difference in Ang II and ACE binding between normal and degenerative canine mitral valves. 86 Ang II has been shown to directly increase expression of TGFb1 in human isolated cardiac fibroblasts. 87 ACE inhibition was found to inhibit TGFb3 synthesis in cultured canine mitral VIC.…”
Section: Angiotensin IImentioning
confidence: 98%
“…Suggested reasons for the non–significant findings in the clinical trials include lack of activation of circulating RAAS activity in asymptomatic MMVD dogs (Häggström and others 1997), low concentration of angiotensin II receptors in the canine mitral valve (Mow and Pedersen 1999) or poor effect of ACE inhibitors on myocardial remodelling and progressive ventricular remodelling in MR (Häggström and others 1996a, Dell'Italia and others 1997). Indeed, more recent research has shown that myocardial remodelling caused by MR is a very complex process, which does involve angiotensin II, but is very difficult to counteract even if ACE and/or angiotensin II receptors are blocked (Perry and others 2002).…”
Section: Therapy Of Asymptomatic Mrmentioning
confidence: 99%